중국 인터넷 공간에서 보편적 가치의 실현 가능성 - 이희경(李喜卿)(Lee Hee-Kyung) (중국학(구중국어문론집), 2020)
사상초유의 대통령 탄핵을 경험한 한국사회에서 인터넷은 소통의 새로운 방식이자 공간의 확장으로 여겨진다. 그러나 중국의 인터넷 공간은 한국과는 사뭇 다른 방향으로 발전하고 있다. 표현의 자유보다는 ‘인터넷 주권’이 우선시되기 때문에 국가 안보를 위협하는 요소들은 모두 검열과 차단의 대상이 되고 있다. 인터넷 만리장성(Great Firewall of China)의 구축, 구글·페이스북·트위터 등 글로벌 인터넷 기업들의 퇴출과 중국 IT 기업의 부상은 중국 내 인터넷 통제가 더욱 견고해지고 치밀해지는 과정을 여실히 보여준다. 이와 동시에 중국정부는 경제발전에 핵심적 역할을 담당하는 인터넷 산업을 발전시키기 위해 적극적인 지원을 아끼지 않고 있다. 정부의 지원에 힘입어 중국은 모바일 결제 시스템, 공유경제 시장에서 타의 추종을 불허하는 성장세를 보이고 있다. 본고는 중국의 사례를 통해 인터넷 공간이 국가권력에 의해 어떻게 재영토화되는지와 공간이론으로 설명하기 힘든 중국식 가상공간의 확장을 살펴보고, 중국을 포함한 전 세계적 가상공간이 보편성을 획득하기 위해 갖추어야 할 선행조건에 대해 고민해보고자 한다. 아울러 서구 철학사와 물리학사에서 논의되어온 절대적 공간 개념 및 상대적 공간 개념이 중국의 인터넷 공간에서도 적용 가능한지를 짚어봄으로써 중국의 인터넷 공간이 지니는 특성에 대해 논의하고자 한다. The internet is considered to be a novel method of communication as well as an extension of space in South Korean society, which has experienced an unprecedented impeachment of the president. On the other hand, China’s internet cyberspace is expanding in a much different direction. As internet sovereignty is prioritized over freedom of expression, any factors that threaten national security become targets of inspection and interception. The formation of the Great Firewall of China, the dismissals of global internet businesses such as Google, Facebook, and Twitter, along with the rise of Chinese IT businesses, clearly represents the process by which the internet control is solidified and tightened in China. At the same time, the Chinese government is providing active support to grow the internet industry, which plays a critical role in economic development. On account of governmental support, China has shown unparalleled growth in the mobile payments system and the sharing economy market. This paper looks at the reterritorialization of internet cyberspace by the government power and the Chinese expansion of cyberspace, which is challenging to explain with spatial theories, and considers the prerequisites for cyberspaces around the world, including China, to obtain universality. Furthermore, it aims to discuss the characteristics of the internet space in China by examining the possibility of applying the concepts of absolute space and relative space, which have been discussed in the Western histories of philosophy and physics, to the Chinese internet cyberspace. KCI Citation Count: 0